The genome sequence of the Bulrush Veneer, Calamotropha paludella (Hübner, 1824) - Boyes, D; Holland, PWH (F1000Research, 2023)
We present a genome assembly from an individual male Calamotropha paludella (the Bulrush Veneer; Arthropoda; Insecta; Lepidoptera; Crambidae). The genome sequence is 742.5 megabases in span. Most of the assembly is scaffolded into 30 chromosomal pseudomolecules, including the Z sex chromosome. The mitochondrial genome has also been assembled and is 16.3 kilobases in length. Gene annotation of this assembly on Ensembl identified 21,500 protein coding genes.